CHILDREN ARE MORE EXPOSED TO ELECTROMAGNETIC RADIATION IN COVID-19 LOCKDOWN: A LITERATURE REVIEW - Sibel Karaca (The Indonesian Journal of Public Health, 2023)
Introduction: The COVID-19 pandemic has significantly affected people's quality of life. Unfortunately, the epidemic continues in various variants and it remains unclear how long it will continue. Children staying at home in the COVID-19 quarantine spent hours in front of the screen with online education. In addition, since they could not go out, they spent their free time in front of the screen using social media, playing computer games or watching movies. The aim of this study is to investigate the effects of low-level electromagnetic radiation (EMR) that children are exposed to at home during the COVID-19 quarantine. Method: The research method is literature review. Results: Studies have shown that, during the quarantine period, children's use of telecommunication devices such as televisions, tablets, smartphones and computers greatly increases. It was determined that the range of radio frequency (RF), Wi-Fi, power lines, visible light and Bluetooth increased in the home environment. The electric and magnetic fields emitted from these devices contain EMR and can seriously harm the health of children, who are structurally more sensitive than adults. Conclusion: There are growing concerns that children staying at home during the COVID-19 pandemic will face health hazards in the future as they are more exposed to EMR.